Challenges and potential improvements in the admission process of patients with spinal cord injury in a specialized rehabilitation clinic - an interview based qualitative study of an interdisciplinary team - Fabian Röthlisberger; Stefan Boes; Sara Rubinelli; Klaus Schmitt; Anke Scheel-Sailer (BMC, 2017)
Abstract Background The admission process of patients to a hospital is the starting point for inpatient services. In order to optimize the quality of the health services provision, one needs a good understanding of the patient admission workflow in a clinic. The aim of this study was to identify challenges and potential improvements in the admission process of spinal cord injury patients at a specialized rehabilitation clinic from the perspective of an interdisciplinary team of health professionals. Methods Semi-structured interviews with eight health professionals (medical doctors, physical therapists, occupational therapists, nurses) at the Swiss Paraplegic Centre (acute and rehabilitation clinic) were conducted based on a maximum variety purposive sampling strategy. The interviews were analyzed using a thematic analysis approach. Results The interviewees described the challenges and potential improvements in this admission process, focusing on five themes. First, the characteristics of the patient with his/her health condition and personality and his/her family influence different areas in the admission process. Improvements in the exchange of information between the hospital and the patient could speed up and simplify the admission process. In addition, challenges and potential improvements were found concerning the rehabilitation planning, the organization of the admission process and the interdisciplinary work. Conclusion This study identified five themes of challenges and potential improvements in the admission process of spinal cord injury patients at a specialized rehabilitation clinic. When planning adaptations of process steps in one of the areas, awareness of effects in other fields is necessary. Improved pre-admission information would be a first important step to optimize the admission process. A common IT-system providing an interdisciplinary overview and possibilities for interdisciplinary exchange would support the management of the admission process. Managers of other hospitals can supplement the results of this study with their own process analyses, to improve their own patient admission processes.